(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
A novel manganese (II) tartrate-based coordination polymer, [Mn2(μ4-Tar)(μ3-Tar)(H2O)]n·3H2O (Tar =tartrate), was characterized by Fourier-transform infrared (FT-IR) spectroscopy in the range of 4000-400 cm-1. The spectrum exhibited a broad absorption band at 3326 cm-1 corresponding to O-H stretching vibrations of coordinated and lattice water molecules as well as hydroxyl groups involved in hydrogen bonding. Strong absorption bands observed at 1555 and 1374 cm-1 were assigned to the asymmetric and symmetric stretching vibrations of coordinated carboxylate groups, respectively. The difference between these bands (Δν=181 cm-1) indicates the participation of carboxylate oxygen atoms in coordination with Mn (II) centers. Furthermore, absorption bands in the 592-522 cm-1 region were attributed to Mn-O stretching vibrations, confirming the formation of metal-oxygen coordination bonds. The FT-IR results support the successful synthesis of a manganese–tartrate coordination polymer containing μ4- and μ3-bridging tartrate ligands.